1982
DOI: 10.1073/pnas.79.3.898
|View full text |Cite
|
Sign up to set email alerts
|

Modification of age-related immune decline in mice dietarily restricted from or after midadulthood.

Abstract: Although weaning-initiated dietary restriction of rodents is known to increase maximum survivorship and inhibit spontaneous late-life disease and immunologic aging, restriction begun in adulthood has been much less thoroughly evaluated. In the present studies, male mice ofa long-lived F1 (4)(5)(6) and is the only strategy known to slow age-related increases in mortality rates in homeotherms (7). Restriction also inhibits or delays (or both) the occurrence of many late-life diseases (8)(9)(10)(11) and retard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
1
1

Year Published

1990
1990
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(47 citation statements)
references
References 19 publications
3
42
1
1
Order By: Relevance
“…In conclusion, the present findings document that dietary restriction is capable of a positive modulation of the synaptic dynamic morphology which may be due to the many reported effects of a reduced caloric intake on free radical generation and/or control (4,6,7,(35)(36)(37)(38)(39)41).…”
Section: Discussionsupporting
confidence: 63%
“…In conclusion, the present findings document that dietary restriction is capable of a positive modulation of the synaptic dynamic morphology which may be due to the many reported effects of a reduced caloric intake on free radical generation and/or control (4,6,7,(35)(36)(37)(38)(39)41).…”
Section: Discussionsupporting
confidence: 63%
“…A reduction of visceral fat has also been reported in such rats [16,17]. These observations are significant in terms of our understanding of the impact of exercise; however, the observation periods (4-8 weeks), which are equivalent to 2-4 years in humans, may have been insufficient to elucidate the impact of habitual exercise [18,19]. Female A/J mice have about a 2-year mean life-span [20]; thus, 24 weeks is equivalent to one-fourth of their life-span.…”
Section: Introductionmentioning
confidence: 79%
“…We believe that the duration of voluntary exercise, 6 months, is the longest of any mouse experiments performed to date. One month for rodents may be equivalent to 2 years for humans [18,19]. The 6-month duration of the exercise period for mice in our study is equivalent to more than 10 years for humans; therefore, the duration was considered to be appropriate to evaluate the effects of exercise on biological markers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Age-associated malignancies which contribute to early death have been correlated with decreased immune activity [7]. Weindruch et al [24,25] have suggested that immunological consequences of food restriction may contribute to of f ectson longevity and late-life spontaneous cancer. Hence, we have examined the effects of food restriction on immune system function and prolongation of life span in GF and SPF mice, yielding the following information on immunological function.…”
Section: Disussionmentioning
confidence: 99%